Implementation of Blended Learning Based on E-Learning in the e-guru.id Community Semarang - Abdul Rohman; Purwosiwi Pandansari (Multimatrix, 2023)
Digital transformation in education encourages teachers to master innovative learning technologies. Digital teacher communities such as e-guru.id play a strategic role in facilitating the development of digital pedagogical competencies through the implementation of blended learning. This study aims to analyze the implementation of e-learning-based blended learning in the e-guru.id Semarang community, identify the platforms and strategies used, and explore the challenges and their impact on teacher competence. The research employed a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of 30 teacher members of the e-guru.id Semarang community. Data analysis was conducted descriptively qualitatively using the Miles and Huberman interactive model. The results showed that the e-guru.id Semarang community implemented a blended learning model with a combination of synchronous learning through Google Meet and Zoom, as well as asynchronous learning using Google Classroom, Moodle, and WhatsApp as supporting media. The implementation of blended learning in this community proved effective in increasing teachers' digital pedagogical competence by 76%, expanding access to collaboration among members, and improving the ability to design technology-based learning. However, challenges faced include limited internet access (43%), digital literacy gaps (35%), and time constraints (22%). The e-guru.id Semarang community has successfully become a model of a professional learning community that supports the sustainable development of teachers in the digital era. Keywords: blended learning, e-learning, teacher community, e-guru.id, digital competence